Why don't Alzheimer's disease patients know that they forget?. (31st December 2021) - Razafimahatratra, Solofo; Guieysse, Thomas; Medani, Takfarinas; Lejeune, François‐Xavier; Houot, Marion; George, Nathalie; La Corte, Valentina; Klarsfeld, André; Dreyfus, Gérard; Pantazis, Dimitrios; Dubois, Bruno; Andrade, Katia
Abstract: Background: Alzheimer's disease (AD) patients are often unaware of their memory deficits even at early stage of disease. Anosognosia has been related to frontal dysfunction although its underlying neural mechanism is still unknown. We hypothesized that it may result from an inability to monitor ongoing behavior due to a failure in the error‐monitoring system. Our main objective was to study this system in individuals at risk for AD. Method: The study involved the 318 cognitively normal individuals of the INSIGHT cohort. All were age 70 and over at entry with a known brain amyloid status assessed by PET. We recorded the error negativity (ERN) and error positivity (Pe) of event‐related potentials (ERPs) in each of these individuals annually over 5 years. The cognitive task was the recognition of words, which had been memorized one hour before. ERPs were obtained by averages that were time‐locked to the erroneous response. All differences were tested through linear mixed‐effects models with group (Prog A+, NotProg A+; i.e., amyloid positive individuals who progressed or not to AD) and time (M0, M60, or Mdiag; i.e., months from study admission or month of AD diagnosis), as well as interaction between both as fixed effects, the subject identifier as a random effect to account for the paired measurements at M0 and M60 or Mdiag, and inclusion of age at M0 for covariate adjustment. Post hoc tests were performed on the interaction. Result: Our study focused on two subgroups identified after 5 years of follow‐up: 1) amyloid positive (A+) individuals who progressed to AD (Prog A+, n=15); and 2) A+ individuals who did not progress to AD (NotProg A+, n=35). When compared to M0 for intragroup analysis or to M60 for intergroup analysis, the Prog A+ group at Mdiag displayed significantly slower reactions and higher error rates, and its Pe amplitude was also significantly lower. Conclusion: Our results indicate the existence of a monitoring system failure in early stages of AD, which may be the substrate of anosognosia.